To rewrite the equation \( \frac{4x}{3x-12} + 3 = 10 \) in two equations joined by "and," we can first isolate the fraction on one side of the equation.
-
Start with the original equation: \[ \frac{4x}{3x - 12} + 3 = 10 \]
-
Subtract 3 from both sides: \[ \frac{4x}{3x - 12} = 10 - 3 \] This simplifies to: \[ \frac{4x}{3x - 12} = 7 \]
Now, we can write the equation as two separate equations:
-
The first equation is the isolated fraction: \[ \frac{4x}{3x - 12} = 7 \]
-
The second equation is the derived part: \[ 3x - 12 \neq 0 \]
So, we can combine these into the final form:
\[ \frac{4x}{3x - 12} = 7 \quad \text{and} \quad 3x - 12 \neq 0 \]